STUDY OF THE RELIABILITY AND OPTIMIZATION OF THE AUTOMATED ROLLING STAMPING COMPLEX - SHTUTS, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The reliability of technical objects is one of their most important quality characteristics. Automated rolling stamping complexes are widely used in mechanical engineering for the manufacture of parts of complex shape. Reliability of CABs is a key factor that determines their efficiency and cost-effectiveness. The development of a device for automatically changing the equipment of the stamping-rolling complex is due to the need to increase efficiency and automate production processes in industry. Roll stamping is an important technology for the production of metal parts, but the process of changing equipment (for example, tools or dies) can be time- and resource-intensive. The development of an automatic equipment changer can significantly improve the productivity and efficiency of production lines, reduce equipment downtime and manual labor costs. In addition, such a device can increase occupational safety and reduce the risk of injury among workers. Since modern industry is rapidly developing and constantly improving production technologies, the development of a device for automatically changing equipment for a stamping-rolling complex is an urgent and important task. The implementation of such a device can help enterprises maintain a competitive edge in the market and increase their efficiency and profitability. The article deals with the reliability of the automated rolling stamping complex, which is one of the key aspects of modern production. Factors affecting the reliability of such systems and ways to increase them to ensure smooth operation of production lines are analyzed. The article reveals the main problems associated with equipment failures and downtime, which can lead to significant financial losses and loss of reputation of the enterprise. The impact of such factors as the intensity of operation, maintenance, as well as the introduction of the latest management and monitoring technologies on the overall reliability of the system was analyzed. The article proposes a comprehensive approach to increasing the reliability of automated rolling stamping complexes. This approach includes optimization of operating modes, improvement of maintenance and diagnostics systems, as well as the use of advanced management technologies and equipment condition monitoring. The results of the research can be useful for factories that use automated rolling stamping complexes in their activities. They will make it possible to increase the efficiency of the production process, reduce the costs of maintenance and repair, as well as ensure the stable and uninterrupted operation of production lines.